Hubungan Pola Asuh Orang Tua dengan Perkembangan Sosial Emosional Anak Pra Sekolah di PAUD Surya Ceria Aisyiyah Kabupaten Karanganyar - Puji Rahayu; Dewi Kartika Sari (Jurnal Medika Nusantara, 2025)
The preschool period is an important period in a child's development, because not all children can go through a period of optimal growth and development. World Health Organization (WHO) 2019, reported that 5-25% of preschool age children experience emotional development disorders with a child population of 23,979,000. Parental parenting patterns really help children achieve normal growth and development according to their age level. The aim of this research is to determine the relationship between parental parenting patterns and the social emotional development of preschool children at PAUD Surya Ceria Aisyiyah Karanganyar. This research method is correlational analytical with a cross sectional approach. The population of this study was 60 people with sampling using the total sampling technique. The results showed that the majority of mothers implemented democratic parenting as many as 48 (80.0%) and the majority of preschool children had very good social emotional development as many as 44 (73.3%). ) preschool children. The data was processed using the chis square test with a value of r value = 0.00 so it can be interpreted that there is a relationship between parenting patterns and the social emotional development of preschool children. Conclusion: Each parent has a different parenting style and each parenting pattern can shape the child's social emotional development differently.